Distribution Characteristics and Environmental Response of Diatoms Deposited in Reservoirs in the Source Region of Le'an River - YIN Hongwei; ZHANG Jie; YAN Ruyu; JI Yong; XIAO Weiqi; CAI Gaotang (Renmin Zhujiang)
At present, the study of heavy metal pollution in the Le'an River Basin should be explored.To fully elucidate the environmental characteristics and change-driven processes of reservoirs in the source region of the Le'an River, this paper employs Qinghua and Shijing reservoirs with different ecological environments and development backgrounds as research objects.Experimental records of diatom species and physicochemical indicators in sedimentary column cores are conducted, and meanwhile combined with modern monitoring data and multivariate statistical methods, environmental characteristics driving factors affecting changes in sedimentary diatom assemblages and sedimentary environment in reservoirs are analyzed.The results show that nutrient levels in the reservoirs gradually increase with the depth to the surface, and the sediment pollution evaluation also reveals the collection process of nutrients.Universal and cleaning indicator species have been replaced by fouling-tolerant and eutrophication indicator species of sedimentary diatoms, with representative species being Achnanthidium minutissima and Navicula minima.The multivariate statistical analysis results show that TP, TN, TP, and TOC are the main driving factors of diatom community structure distribution in Qinghua and Shijing reservoirs respectively (p<0.05).Box plot analysis results of 18 diatom indices reveal that CEE and LOBO indices are screened and show sound evaluation suitability and correlation.The input of exogenous materials into the reservoirs is affected by different anthropogenic practices to drive the succession of the diatom community, with a trend towards eutrophication in both reservoirs.